GAMBARAN PAPARAN DEBU DAN FUNGSI PARU PADA PEKERJA PEMBUATAN PERABOT RUMAH TANGGA DI CV KOCHI SOHOR TERJUN MEDAN MARELAN TAHUN 2013 - Eva Yolanda Purba; Halinda Sari Lubis; Umi Salmah (Lingkungan dan Kesehatan Kerja, 2013)
Description of dust exposure and lung function in workers home furnishings maker on CV Kochi Sohor Terjun North Sumatera in 2013. The dust exposure in the working environment indirectly may result in variously disorder on health, one of them is a respiratory disorder that since then it is going to impact one’s productivity. Noted that respiratory disorder might be influenced by amount the dust level around working environment and the worker’s attitude over wood’s dust exposure perhaps by using one’s self protecting tool (APD), working service, previously illness history, smoking history of the worker. This study aims to know whether the influence of the wood’s dust exposure against the function of wood of those workers in furniture with informal sector on CV Kochi Sohor Terjun Medan Marelan. The research adopted an description with sectional across approaching. It is involved 6 samples taken out population presented while conducting the field research. In collecting the data, the writer provided questionnaire, with tester of dust level in a High volume sampler, and the tool to measure the function of lungs there used Spirometer Sibelmed Datospir Mod 120B. The result of this research seen by a 2 working area measured that not exceeding the total dust level above quality standard of the Area of wood folding 4.53 mg/m3, and the refinery site 2.38 mg/m3 (< 10 mg/m3 NAB). The respondent got lowering function of lungs in a light restrictive 4 people and another 1 got reducing function of lungs in moderate restrictive. The result of bi-variant indicated no found any relation between the uses APD, working service, previous illness history, age, smoking history with reduced function of lungs. It is expected having a health check over all workers whose got reducing function of lungs or not and for not getting deteriorated function of lungs. Keywords : wood’s dust level, reducing function of lungs